Plasma Electrolytic Oxidation of Binary Al-Sn Alloys - Gencer, Y.; Tarakci, M.; Gulec, A. E.; Oter, Z. Cagatay (Polish Acad Sciences Inst Physics, 2014)
Binary Al-Sn (1, 2, 4, 6, 8 at.% Sn) synthetic alloys were prepared under vacuum-atmosphere controlled furnace. The Al-Sn alloys were coated by plasma electrolytic oxidation technique for 120 min in aqueous electrolyte containing sodium silicate and potassium hydroxide using the same electrical parameters. The microstructure, surface roughness, phase content and chemical composition of the coatings were characterized by scanning electron microscopy, profilometry and X-ray diffractometry. The coating became porous while coating thickness and surface roughness decreased, with increasing amount of Sn content in Al-Sn alloys. The coating was not formed on the Al-Sn alloy with 8 at.% Sn. Plasma electrolytic oxidation coatings were composed of mainly mullite (3Al(2)O(3)center dot 2SiO(2)), gamma-Al2O3 and alpha-Al2O3 up to 4 at.% Sn. The alpha-Al2O3 phase formed as precipitate in the inner region of the coating and its amount decreased with Sn amount in the Al-Sn alloys. The SnO2 phase was only detected in the coating of Al-6Sn alloy. Scanning electron microscopy - energy dispersive X-ray spectroscopy results showed that the traces of Sn were evident in the oxide coating along with Al, O, Si, Na, and K. The increasing addition of Sn in the alloys resulted in reduction of the overall microhardness of the coating with decreasing manner from dense inner region to the surface of the coatings.
3rd International Congress on Advances in Applied Physics and Materials Science -- APR 24-28, 2013 -- Antalya, TURKEY
Keywords: Corrosion-Resistance; Aluminum-Alloy; Coatings; Wear